PENGARUH PEMBELAJARAN DARING GOOGLE CLASSROOM TERHADAP MINAT BELAJAR MATA PELAJARAN AKUNTANSI DASAR - Nely Hartika; Fitri Nurlaili; Parida Ratna (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
The purpose of this study was to find out the influence of Google Classroom online learning on the learning interests of x-class students on basic accounting lessons at SMK Negeri 1 Kragilan Kab. Serang. Research methods were used with quantitative techniques and data collection techniques using questionnaires, documentation, library studies. In this study first conducted instrument testing, namely by conducting a validity and reliability test, then conducting a data normality test, a simple linear regression test, a hypothesis test (T Test) and a determination coefficient test using SPSS 26. Based on the results of the T Test (hypothesis) obtained the value Tcalculated 4.923 while the Ttable 1.99601. This indicates that T Test > Ttable or 4.923 > 1.99601, so H0 was rejected, and Ha was accepted. So, it can be concluded that there was an influence of online learning with Google Classroom on the interest in learning basic accounting subjects (in students of class x SMK Negeri Kragilan).